Pengaruh Gaya Kepemimpinan, Komunikasi dan Disiplin Kerja terhadap Kinerja Karyawan pada CV. Bintang Tex Indonesia - Wardha Firdailla; Enny Widyaningrum; Anggraeni Rahmasari (Universitas Bhayangkara Surabaya, 2021)
The purpose of this study was to determine and analyze whether the variables of leadership style, communication, and work discipline simultaneously and partially affect the performance of employees of CV. Bintang Tex Indonesia. And to find out which variables of leadership style, communication and work discipline that influence dominantly on the performance of employees of CV. Bintang Tex Indonesia. Hypothesis testing is done based on quantitative tests with statistical test equipment, measuring variables using a Likert scale type by distributing questionnaires. The population in this study were the employees of CV. Bintang Tex Indonesia. The sampling technique is done by using the saturation sampling technique. The sample of this study was 60 people. The data technique uses multiple linear regression. After conducting research and analysis it can be concluded that the leadership style, communication and work discipline variables have a significant and partial effect on employee performance on the CV. Bintang Tex Indonesia. While the dominant results are based on the beta coefficient value of each leadership style variable (X1) 0.181, communication (X2) 0.509, and work discipline (X3) 0.296. Then the communication variable (X2) dominant effect on employee performance CV. Bintang Tex Indonesia.